Registration of 'Pritchett' Soft White Winter Club Wheat. Issue 2 (27th April 2017) - Garland-Campbell, Kim; Carter, Arron H.; Jones, Stephen S.; Chen, Xianming; DeMacon, Patricia; Higginbotham, Ryan; Engle, Doug; Guy, Stephen O.; Mundt, Chris C.; Murray, Timothy D.; Morris, Craig F.; See, Deven
Abstract : Soft white club wheat ( Triticum aestivum ssp. compactum ) is a unique component of wheat production in the Pacific Northwest, comprising 10 to 12% of the wheat crop. It is valued for milling and baking functionality and marketed for export in a 10 to 30% blend with soft white wheat known as western white. Our goal was to develop a club wheat cultivar for the traditional club wheat‐growing region of central Washington, with better soilborne disease resistance than currently grown cultivars. The bulk pedigree breeding method was used to select Pritchett (Reg. No. CV‐1123, PI 678944) from the cross: 'Chukar'/2*'Bruehl'. Pritchett has significantly better grain yield and grain volume weight in environments receiving less than 30 cm annual precipitation than Bruehl, the cultivar that it is targeted to replace. Pritchett has better milling quality, producing larger diameter cookies and greater volume sponge cake. Pritchett has effective adult plant resistance to stripe rust, has moderate resistance to Cephalosporium stripe, and carries the Pch1 gene for moderate resistance to eyespot. Pritchett carries the Rht‐B1b allele for reduced plant height but has excellent emergence from deep sowing. Pritchett was released because of its superior agronomic productivity in the targeted region, combined with resistance to multiple diseases and superior end use quality.